Wybrane innowacje kulturowe we współczesnej polskiej myśli religijnej - Iwanicki, Juliusz (Polskie Towarzystwo Religioznawcze, 2016)
The article analyses the concept of cultural innovation. Some elements of this process are distinguished: (1) the development of the idea in the mind of the creator; (2) transfer of the idea materialized in the form of the work; (3) obtaining recognition from customers; (4) imitation of the works from the epigones. An example of such an innovation is the blog Cleopas published in the Polish network. The specificity of this Website makes that it promotes various innovative attempts of cultural works. The main developer of this portal, Robert Rynkowski, promotes various innovations within theology and seeks to critically approach many phenomena in Polish religious thought promoting cultural stagnation. He also has published a book, which makes an attempt to deepen inclusive religiosity, inter alia, by the idea that everyone is a theologian, or that there are different types of religious thought (academic, secular, artistic, etc.). The second innovative religious thinker presented in this article is Waclaw Hryniewicz. He also participates in discussions on the aforementioned online blog. In addition, it promotes the so-called theological hypothesis about the hope of universal salvation. The above-mentioned examples of cultural innovation in the Polish religion are not the dominant voice of Polish Catholicism. The Polish Catholic Church also promotes more exclusive stance, which attaches greater significance to the defence of religious tradition.
Keywords: innowacja w kulturze; Innowacja kulturowa w myśli religijnej; blog Kleofas; Wacław Hryniewicz; Robert Rynkowski; kultura sieciowa